Strategy Analysis of Laying Chicken Business Development in Semarang City (Business and Economic Analysis Journal, 2021)
The business of laying hens has a strategic position in improving the quality of human resources through the provision of animal protein and improving the welfare of the farming community. This study aims to analysis the internal and external factors that must be faced by farmers in business development and competition in the city of Semarang and to formulate alternative strategies for developing laying hens that are appropriate to be implemented in the city of Semarang. This research is a descriptive study with a qualitative approach, the researcher analysis business strategies through a SWOT analysis which includes: strengths, weaknesses, opportunities and threats faced by entrepreneurs in increasing the competitiveness of laying hens breeders in Semarang City. The core strategy that can be applied by laying hens in the city of Semarang is the strategy Growth and Build (grow and develop) through an intensive strategy or an integration strategy. Based on the position, livestock in the city of Semarang is in quadrant I in the IE matrix, which illustrates that the livestock business in the city of Semarang is in an average internal condition and the response to external factors is high.